Hubungan Pengetahuan Ibu Tentang 1000 Hari Pertama Kehidupan Dengan Kejadian Stunting - Sari, Niken Ayu; Yanti, Mira (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: The World Health Organization (WHO) states that children under five in the world experience stunting problems where the number of stunting in Indonesia is in the top 5 countries in the world. The problem of fulfilling nutrition in the first 1,000 days of life (HPK) faced by mothers in Indonesia is one of the factors that causes problems in children's growth and development, one of which is stunting. Knowledge of 1,000 HPK is important, especially during the growth and development period of children starting from 0 days of pregnancy to 2 years old. Knowledge will increase along with the mother's attitude regarding fulfilling balanced nutrition. Methods: This type of research is quantitative descriptive research with a cross sectional approach. This research was conducted in Yangapi Village, Tembuku Bangli District. The population in this study was 237 mothers with toddlers aged 0-24 months. The sampling technique used is non-probability sampling with purposive sampling type. Data analysis used the Spearman Rank Correlational test with an error rate of 5% (0.05). Results: The results of the study showed that the majority of mothers had sufficient knowledge, namely 77 people (51.7%), the majority of toddlers were in the normal category, namely 135 toddlers (90.6%). The results of the analysis obtained a p-value of 0.011, where the p-value is less than the p-value of 0.05, which means there is a relationship between the mother's level of knowledge about 1000 HPK and the incidence of stunting in toddlers. Conclusion: Mother's knowledge influences food consumption patterns, especially toddlers. Lack of knowledge about nutrition results in low food diversity and quality. Nutritional disorders are also caused by the mother's lack of ability to apply information about the 1000 HPK in daily life.